In Search of Adequate Principles for AI Civil Liability - Gredka-Ligarska, Iwona (PRAWO i WIĘŹ, 2024)
This paper examines the civil liability of AI systems in EU legislation. The analysis discusses current problems with AI liability, proposals of the European Union legislator on how to solve existing problems and includes de lege ferenda suggestions. The observations’ conclusions allow us to answer whether the legal solutions offered by the Products Liability Directive proposal and the AI Liability Directive proposal are adequate to the identified problems with the liability of AI systems.